Motor Cortical Network Plasticity in Patients With Recurrent Brain Tumors - Bulubas, Lucia; Sardesh, Nina; Traut, Tavish; Findlay, Anne; Mizuiri, Danielle; Honma, Susanne M.; Krieg, Sandro M.; Berger, Mitchel S.; Nagarajan, Srikantan S.; Tarapore, Phiroz E. (Frontiers in Human Neuroscience, 2020)
Objective: The adult brain’s potential for plastic reorganization is an important mechanism for the preservation and restoration of function in patients with primary glial neoplasm. Patients with recurrent brain tumors requiring multiple interventions over time present an opportunity to examine brain reorganization. Magnetoencephalography (MEG) is a noninvasive imaging modality that can be used for motor cortical network mapping which, when performed at regular intervals, offers insight into this process of reorganization. Utilizing MEG-based motor mapping, we sought to characterize the reorganization of motor cortical networks over time in a cohort of 78 patients with recurrent glioma. Methods: MEG-based motor cortical maps were obtained by measuring event-related desynchronization in ß-band frequency during unilateral index finger flexion. Each patient presented at our Department at least on 2 occasions for tumor resection due to tumor recurrence, and MEG-based motor mapping was performed as part of preoperative assessment before each surgical resection. Whole-brain activation patterns from first to second MEG scan (obtained before first and second surgery) were compared. Additionally, we calculated distances of activation peaks, which represent the location of the primary motor cortex (MC), to determine the magnitude of movement in motor eloquent areas between the first and second MEG scan. We also explored which demographic, anatomic, and pathologic factors influence these shifts. Results: The whole brain activation motor maps showed a subtle movement of the primary MC from first to second timepoint, as was confirmed by determination of motor activation peaks. The shift of ipsilesional MC was directly correlated with a frontal-parietal tumor location (p < 0.001), presence of motor deficits (p = 0.021), and with a longer period between MEG scans (p = 0.048). In addition, a disengagement of wide areas in the contralesional (ipsilateral to finger movement) hemisphere at second timepoint was observed. Conclusions: MEG imaging is a sensitive method for depicting plasticity of the motor cortical network. Although the location of the primary MC undergoes only subtle changes, appreciable shifts can occur in the setting of a stronger and longer impairment of the tumor on the MC. The ipsilateral hemisphere may serve as a reservoir for functional recovery.